Difference in plantar pressure between the preferred and non-preferred feet in four soccer-related movements - Wong, P.; Chamari, K.; Chaouachi, A.; Mao, D. W.; Wisloff, U.; Hong, Y. (British Journal of Sports Medicine, 2007)
Objective and participants: The present study measured the difference in plantar pressure between the preferred and non-preferred foot in four soccer-related movements in 15 male university soccer players (mean (SD) age 20.9 (1.3) years, mean (SD) height 173 (4) cm and mean (SD) weight 61.7 (3.6) kg).